Penerapan Composite Logic dalam Mengkolaborasikan Framework Terkait Multimedia Forensik - Nora Lizarti; Bambang Sugiantoro; Yudi Prayudi (JISKA (Jurnal Informatika Sunan Kalijaga), 2017)
Like the digital forensics in general, multimedia forensics requires an integrated and flexible framework that can guide the process of proof is procedurally in order to maintain the validity of a digital evidence so that it can be justified in court. But this time, the digital forensics investigation framework that develops more emphasis on computer forensic investigations in general and did not give a specific stage of multimedia forensics. Often in investigating multimedia forensics investigator uses a framework that vary depending on the type of multimedia content to be analyzed, of course it becomes inflexible and inefficient, whereas multimedia content share characteristics that allow it to be integrated into a single unit. This study develops a forensic multimedia framework by implementing the Composite Logic to collaborate on several multimedia framework and related documents. Logic Composite method is a method of modeling the distribution of structured logical modularization techniques with explicit interface in which a model consists of a set of components that are interconnected with the principle of decomposition. In other words, the application of this method will allow researchers to extract and merge several frameworks into a single unit does not eliminate the function and the basic structure of the frameworks.